An overview of the potential impacts of interventions on diverse coffee agroforestry system to gender dynamics in Pagar Alam District, South Sumatera - Mulyoutami, E.; Martini, E.; Roshetko, J.M. (World Agroforestry Centre, 2021)
This study was conducted through interviews (in-depth and semi-structured interview) and focus group discussions with coffee households and farmers in Pagar Alam District from September to October 2020. Two subdistricts were selected as focused study sites. These two subdistricts have received intervention from a project to enhance coffee farmers livelihood through diverse agroforestry systems, named Empower Project that has been running in the subdistricts since 2018. In total, 125 respondents were interviewed through semi-structured interviews to understand gender dynamics at the household level. Eight key informants were interviewed to understand the type of agroforestry interventions implemented and how they perceived it. To triangulate the interview data results, a series of four focus group discussions (FGD), disaggregated between women and men, were held in 4 villages of the 2 subdistricts. This study deployed a qualitative analysis to generate the results.